The Role Of The Merangin Regency Government Through Welfare Policy In The Globalization Era - HM, Pahrudin (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2019)
The background of this research is related to two things, namely: how the forms of roles that can be carried out by the Merangin Regency Government in the era of globalization and how they affect the welfare of society public. The purpose of this study is to analyze the role of government to improve the welfare of society in the era of globalization. The discourse of globalization gave rise to radical groups who thought that the government did not need to intervene in development because it was carried out by the private sector and were skeptical that it was precisely because of the many negative effects of globalization that it became an important entry point for that role. This study uses a qualitative approach by analyzing public policy from the Merangin District Government and community welfare data. The study results show that local governments play an important role in exploiting opportunities and preventing the negative impacts of globalization. In conclusion through a series of innovative and solutive policies, the Merangin District Government seeks to improve the welfare of the community by utilizing its local potential.Â